Hydrogeochemical and Groundwater Assessment for Drinking Purpose at ITERA Campus Area and Its Surroundings - Siringoringo, Luhut Pardamean; Rizki, Reza; Nababan, Janner (UIR PRESS, 2019)
Groundwater research for drinking purpose was very important to be done at ITERA campus and its surroundings. It is caused the area is very close to social activities, especially for students. The hydrogeochemical analysis was done with integrating Piper diagram plotting result, X-Y plotting result for some cations and anions, and Gibbs diagram plotting result. Groundwater assessment for drinking purpose referred to Peraturan Menteri Kesehatan Republik Indonesia No. 492/MENKES/PER/IV/2010. There were 14 samples that were taken from nine dig wells and five drill wells. The groundwater facieses were dominated by Facies Na-HCO3-Cl (35,71%) followed by Facies Na-Cl (21,43%), Facies Na-HCO3 (21,43%), Facies Na-SO4-Cl (14,29%), dan Facies Ca-Mg-HCO3 (7,14%). Generally, Groundwater hydrogeochemical of research area shows that groundwater chemistries are controlled by minerals weathering, evaporation, and precipitation. There are eight wells that not proper for drinking and six wells that proper for drinking. Integration lab result, stratigraphic analysis, and depth aquifer show that groundwater that proper for drinking comes from confined aquifer while that not proper for drinking comes from unconfined aquifer